2016
DOI: 10.1016/s1473-3099(16)30190-6
|View full text |Cite
|
Sign up to set email alerts
|

Population-based resistance of Mycobacterium tuberculosis isolates to pyrazinamide and fluoroquinolones: results from a multicountry surveillance project

Abstract: SummaryBackgroundPyrazinamide and fluoroquinolones are essential antituberculosis drugs in new rifampicin-sparing regimens. However, little information about the extent of resistance to these drugs at the population level is available.MethodsIn a molecular epidemiology analysis, we used population-based surveys from Azerbaijan, Bangladesh, Belarus, Pakistan, and South Africa to investigate resistance to pyrazinamide and fluoroquinolones among patients with tuberculosis. Resistance to pyrazinamide was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
119
1
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(139 citation statements)
references
References 25 publications
10
119
1
9
Order By: Relevance
“…Resistance to the latest generation fluoroquinolones at the clinical breakpoint is still uncommon, a finding supporting current WHO recommendations to use moxifloxacin or gatifloxacin in the treatment of MDR-TB. 36 …”
Section: Drug-susceptible Tbmentioning
confidence: 99%
“…Resistance to the latest generation fluoroquinolones at the clinical breakpoint is still uncommon, a finding supporting current WHO recommendations to use moxifloxacin or gatifloxacin in the treatment of MDR-TB. 36 …”
Section: Drug-susceptible Tbmentioning
confidence: 99%
“…The efficacy of fluoroquinolones in bulk assays is inversely proportional to the bacterial metabolic state and cell density, not merely due to target unavailability and decreased permeability (Sarathy et al, 2013;Gutierrez et al, 2017), but also for the ability of both replicating and non-replicating cells to repair DNA (Volzing and Brynildsen, 2015). Conversely, M. tuberculosis expresses relatively low levels of recA, also following exposure to fluoroquinolones, and its mutation rate is generally low (O'Sullivan et al, 2008;Zignol et al, 2016;Gagneux, 2018). In model microorganisms, the formation of cells persistent to fluoroquinolones and increased mutation rate were associated with constitutive induction of the SOS response (Dörr et al, 2009).…”
Section: Of 19mentioning
confidence: 99%
“…Data from Pakistan and Brazil showed more optimistic eligibility rates of 50% or higher [11,12]. A multicountry population-based survey showed that, although pyrazinamide resistance was significantly associated with rifampicin resistance, this drug might still be effective in 19-63% of patients with rifampicin-resistant TB, and that the worrisome high level of ofloxacin resistance in Pakistan ( probably reflecting extensive, unregulated use of fluoroquinolones in some parts of Asia) was tempered by the negligible levels of resistance to fourth-generation fluoroquinolones documented in all survey sites [13]. To our knowledge, there are to date no publications on the eligibility of this regimen among patients with MDR-PTB from South-east Asia, India and China.…”
mentioning
confidence: 99%